Preparation method of lithium ion battery
By prelithiation of the negative electrode sheet of lithium-ion battery and modification of the positive electrode material, combined with improved separator technology, the irreversible capacity loss and overcharge safety of lithium-ion batteries during the first charging and discharging are solved, and the use of batteries is significantly improved Lifespan and performance.
Patent Information
- Application Number
- CN202411465454.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-10
AI Technical Summary
The SEI film formed by lithium-ion batteries during the first charging and discharging leads to irreversible capacity loss, and the existing lithium supplementation methods have safety risks and high costs, which can easily cause heat loss during overcharging.
By prelithiating the negative electrode sheet of the lithium-ion battery, a negative electrode sheet with a surface protective layer is formed, and the positive electrode material is modified. Combined with the improved separator manufacturing technology, it is assembled into a lithium-ion battery to reduce SEI impedance and improve the battery. performance.
It significantly improves the service life and cycling performance of lithium-ion batteries, improves the interface stability of the positive electrode material and the thermal stability of the separator, reduces the impedance of the SEI film, and extends the energy density of the battery.
Smart Images

Figure CN119297420A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery production, and in particular to a method for preparing a lithium ion battery. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic products and electric vehicles due to their high energy density and long cycle life. During the first charge of lithium-ion batteries, a SEI film will form on the surface of the negative electrode and consume the active lithium in the positive electrode material, resulting in irreversible capacity loss. At present, the irreversible capacity loss of commercial graphite negative electrode materials can reach 10%, while for silicon-based negative electrode materials and tin-based negative electrode materials with high specific capacity, the irreversible capacity loss is even as high as 30% or more, which greatly reduces the energy density of lithium-ion batteries.
[0003] In order to solve the problem of irreversible capacity caused by the formation of SEI film during the first charge and discharge of the above-mentioned lithium-ion batteries, researchers usually use the method of negative electrode lithium replenishment to overcome it. Among them, the methods of negative electrode lithium replenishment mainly include lithium foil replenishment and lithium powder replenishment, but because lithium metal itself is relatively active, it has high requirements for storage environment and manufacturing environment, so lithium metal has greater safety risks and complex processing risks, and the production cost is high. In addition, although the positive electrode lithium replenishment technology has high safety, the lithium replenishment materials used need to be charged to 4.2V~4.5V to play the corresponding lithium replenishment role, and are prone to cause a series of problems under high voltage conditions, such as electrolyte decomposition and gas production, high temperature burning of the diaphragm, and battery overcharge failure.
[0004] The "overcharge" test item is an important safety indicator for lithium-ion batteries. When a lithium-ion battery is in an overcharged state, the cathode delithiation potential increases rapidly as the overcharge degree increases. When it exceeds a certain limit, it causes irreversible oxidation and decomposition of the electrolyte inside the battery, produces flammable gas and releases a large amount of heat, causing the temperature and pressure inside the battery to rise, and triggering a series of exothermic reactions, which leads to thermal runaway inside the battery.
[0005] Therefore, the above problems need to be solved urgently. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing a lithium-ion battery, which not only solves the problem of large SEI impedance caused by excessive consumption of electrolyte additives, but also can sustainably repair the SEI film, thereby increasing the service life of the lithium-ion battery.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solution: A method for preparing a lithium ion battery of the present invention, the innovation of which is that it comprises the following steps: (1) preparing a negative electrode sheet for a lithium-ion battery and performing a pre-lithiation treatment on the negative electrode sheet to obtain a pre-lithiation negative electrode sheet; (2) In an inert gas environment, placing the pre-lithiated negative electrode sheet in an electrolyte for reaction, and then washing and drying the pre-lithiated negative electrode sheet to obtain a surface protective layer; (3) The positive electrode active material and the salt solution are fully stirred and mixed, and then filtered, dried and heat-treated in sequence to obtain a modified lithium-ion battery positive electrode sheet; (4) coating the coating slurry on the surface of the microporous membrane material, and then drying and curing the slurry to obtain a lithium-ion battery separator; (5) Assembling the pre-lithiated negative electrode sheet with a surface protective layer, the modified lithium-ion battery positive electrode sheet and the lithium-ion battery separator, and then sequentially performing liquid injection, standing, formation and volume separation treatments to obtain a lithium-ion battery.
[0008] Preferably, in the above step (1), the specific process of obtaining the pre-lithiation negative electrode sheet by pre-lithiation treatment is: (1.1) placing the negative electrode sheet of the lithium-ion battery into the first pre-lithiation unit for infiltration treatment; (1.2) placing the negative electrode sheet of the lithium-ion battery after the primary impregnation treatment into the second pre-lithiation unit for secondary impregnation treatment; (1.3) The lithium-ion battery negative electrode sheet after the secondary infiltration treatment is rinsed to obtain a pre-lithiation negative electrode sheet.
[0009] Preferably, in the above step (1.1), the temperature environment of the first pre-lithiation unit is 40° C. to 85° C., and the negative electrode sheet of the lithium-ion battery is immersed in the first pre-lithiation unit for 20 s to 300 s.
[0010] Preferably, in the above step (1.2), the temperature environment of the second pre-lithiation unit is 20° C. to 35° C., and the negative electrode sheet of the lithium-ion battery is immersed in the first pre-lithiation unit for 20s to 360s.
[0011] Preferably, in the above step (1.3), dimethyl carbonate solvent is used for elution.
[0012] Preferably, in the above step (2), the electrolyte is a mixture of a lithium salt and a solvent, the lithium salt is one or more combinations of lithium hexafluorophosphate, lithium tetrafluoroborate and lithium perchlorate, and the solvent is one or more combinations of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
[0013] Preferably, in the above step (2), the reaction time of the pre-lithiated negative electrode sheet in the electrolyte is 20-60 minutes; the washing times are 3-5 times; the drying temperature is 60°C-70°C, and the drying time is 2-3 hours.
[0014] Preferably, in the above step (3), the specific process of obtaining the modified lithium-ion battery positive electrode sheet is: (3.1) The solvent of the salt solution is one or more of methanol and ethanol, and the solute is one or more of lithium, magnesium, aluminum, zinc and chromium, and then the salt solution is prepared, and the concentration of the modified ions in the salt solution is ensured to be 0.1~1.0 mol / L; (3.2) Under continuous stirring, add the salt solution to the positive electrode active material at a rate of 1-10 ml / min, and continue stirring at a stirring rate of 300-1000 r / min for 2-3 hours to obtain the positive electrode material; (3.3) The obtained positive electrode material is first filtered, then dried at a temperature of 50°C to 80°C for 3 to 6 hours, and then heat treated at a temperature of 500°C to 800°C for 3 to 6 hours to obtain a modified lithium-ion battery positive electrode sheet.
[0015] Preferably, in the above step (3.2), the positive electrode active material is one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium vanadium phosphate and lithium manganate.
[0016] Preferably, in the above step (4), the specific process for obtaining the lithium-ion battery separator is: (4.1) firstly, carbon nanotubes with a diameter of 1 to 250 nm and a length of 0.2 to 50 μm are uniformly dispersed in ethanol to obtain a carbon nanotube dispersion in which the carbon nanotubes account for 1 to 30 wt%; (4.2) then uniformly dispersing aluminum oxide with a particle size of 1 to 500 nm in ethanol to obtain an aluminum oxide dispersion in which the aluminum oxide accounts for 1 to 30 wt %; (4.3) Then, the carbon nanotube dispersion and the aluminum oxide dispersion are fully mixed, and during this process, the mass ratio of the carbon nanotubes to the aluminum oxide is controlled to be 0.5-1, thereby obtaining solution I; (4.4) adding polyvinyl alcohol to solution I, and controlling the amount of polyvinyl alcohol to be 0.1-15 wt % of solution I, thereby obtaining solution II; (4.5) Solution II is then heated to 60°C to 80°C and reacted for 2 to 6 hours to fully crosslink the carbon nanotubes and alumina, and then 0.2 to 1 wt% of sodium dodecyl sulfate is added as an auxiliary agent and stirred for 30 minutes to fully mix the carbon nanotubes and alumina to obtain a coating slurry; (4.6) The obtained coating slurry is coated on the surface of the microporous membrane material, and then dried and cured to obtain a lithium-ion battery separator.
[0017] Beneficial effects of the present invention: (1) The present invention not only solves the problem of high SEI impedance caused by excessive consumption of electrolyte additives, but also can sustainably repair the SEI film, thereby extending the service life of lithium-ion batteries; (2) The present invention pre-lithiates the negative electrode sheet of the lithium-ion battery to compensate for the irreversible capacity loss caused by the formation of the SEI film, thereby significantly improving the cycle performance of the battery; (3) The present invention improves the interface stability of the positive electrode material of the lithium ion battery and improves the electrochemical performance of the lithium ion battery by modifying the positive electrode sheet of the lithium ion battery; (4) The present invention significantly improves the thermal stability of lithium-ion battery separators. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 The present invention is a flow chart of a method for preparing a lithium-ion battery. DETAILED DESCRIPTION
[0020] The technical solution of the present invention will be clearly and completely described below through specific implementation methods.
[0021] A method for preparing a lithium ion battery of the present invention, as Figure 1 As shown, the following steps are included: (1) A lithium-ion battery negative electrode sheet is prepared and pre-lithiated to obtain a pre-lithiated negative electrode sheet.
[0022] In the above steps, the specific process of obtaining the pre-lithiation negative electrode sheet through pre-lithiation treatment is as follows: (1.1) placing the negative electrode sheet of the lithium-ion battery into the first pre-lithiation unit for infiltration treatment; The temperature environment of the first pre-lithiation unit is 40° C. to 85° C., and the negative electrode sheet of the lithium-ion battery is immersed in the first pre-lithiation unit for 20s to 300s.
[0023] (1.2) placing the negative electrode sheet of the lithium-ion battery after the primary impregnation treatment into the second pre-lithiation unit for secondary impregnation treatment; The temperature environment of the second pre-lithiation unit is 20° C. to 35° C., and the negative electrode sheet of the lithium-ion battery is immersed in the first pre-lithiation unit for 20s to 360s.
[0024] (1.3) The lithium-ion battery negative electrode sheet after the secondary impregnation treatment is eluted to obtain a pre-lithiated negative electrode sheet; wherein dimethyl carbonate solvent is used for elution.
[0025] (2) In an inert gas environment, the pre-lithiation negative electrode sheet is placed in an electrolyte for reaction, and then washed and dried to obtain a pre-lithiation negative electrode sheet with a surface protective layer.
[0026] In the above steps, the electrolyte is a mixture of a lithium salt and a solvent, the lithium salt is one or more combinations of lithium hexafluorophosphate, lithium tetrafluoroborate and lithium perchlorate, and the solvent is one or more combinations of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
[0027] In the above steps, the reaction time of the pre-lithiated negative electrode sheet placed in the electrolyte is 20 to 60 minutes; the washing times are 3 to 5 times; the drying temperature is 60° C. to 70° C., and the drying time is 2 to 3 hours.
[0028] (3) The positive electrode active material and the salt solution are fully stirred and mixed, and then filtered, dried and heat-treated in sequence to obtain a modified lithium-ion battery positive electrode sheet.
[0029] In the above steps, the specific process of obtaining the modified lithium-ion battery positive electrode sheet is as follows: (3.1) The solvent of the salt solution is one or more of methanol and ethanol, and the solute is one or more of lithium, magnesium, aluminum, zinc and chromium. The salt solution is prepared and the concentration of the modified ions in the salt solution is ensured to be 0.1~1.0 mol / L.
[0030] (3.2) Under continuous stirring, add the salt solution to the positive electrode active material at a rate of 1-10 ml / min, and continue stirring at a stirring rate of 300-1000 r / min for 2-3 hours to obtain the positive electrode material; The positive electrode active material is one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium vanadium phosphate and lithium manganate.
[0031] (3.3) The obtained positive electrode material is first filtered, then dried at a temperature of 50°C to 80°C for 3 to 6 hours, and then heat treated at a temperature of 500°C to 800°C for 3 to 6 hours to obtain a modified lithium-ion battery positive electrode sheet.
[0032] (4) The coating slurry is applied to the surface of the microporous membrane material, and then dried and cured to obtain a lithium-ion battery separator.
[0033] In the above steps, the specific process of obtaining the lithium-ion battery separator is as follows: (4.1) firstly, carbon nanotubes with a diameter of 1 to 250 nm and a length of 0.2 to 50 μm are uniformly dispersed in ethanol to obtain a carbon nanotube dispersion in which the carbon nanotubes account for 1 to 30 wt%; (4.2) then uniformly dispersing aluminum oxide with a particle size of 1 to 500 nm in ethanol to obtain an aluminum oxide dispersion in which the aluminum oxide accounts for 1 to 30 wt %; (4.3) Then, the carbon nanotube dispersion and the aluminum oxide dispersion are fully mixed, and during this process, the mass ratio of the carbon nanotubes to the aluminum oxide is controlled to be 0.5-1, thereby obtaining solution I; (4.4) adding polyvinyl alcohol to solution I, and controlling the amount of polyvinyl alcohol to be 0.1-15 wt % of solution I, thereby obtaining solution II; (4.5) Solution II is then heated to 60°C to 80°C and reacted for 2 to 6 hours to fully crosslink the carbon nanotubes and alumina, and then 0.2 to 1 wt% of sodium dodecyl sulfate is added as an auxiliary agent and stirred for 30 minutes to fully mix the carbon nanotubes and alumina to obtain a coating slurry; (4.6) The obtained coating slurry is coated on the surface of the microporous membrane material, and then dried and cured to obtain a lithium-ion battery separator.
[0034] (5) Assembling the pre-lithiated negative electrode sheet with a surface protective layer, the modified lithium-ion battery positive electrode sheet and the lithium-ion battery separator, and then sequentially performing liquid injection, standing, formation and volume separation treatments to obtain a lithium-ion battery.
[0035] Beneficial effects of the present invention: (1) The present invention not only solves the problem of high SEI impedance caused by excessive consumption of electrolyte additives, but also can sustainably repair the SEI film, thereby extending the service life of lithium-ion batteries; (2) The present invention pre-lithiates the negative electrode sheet of the lithium-ion battery to compensate for the irreversible capacity loss caused by the formation of the SEI film, thereby significantly improving the cycle performance of the battery; (3) The present invention improves the interface stability of the positive electrode material of the lithium ion battery and improves the electrochemical performance of the lithium ion battery by modifying the positive electrode sheet of the lithium ion battery; (4) The present invention significantly improves the thermal stability of lithium-ion battery separators.
[0036] The embodiments described above are merely descriptions of preferred implementation modes of the present invention, and are not intended to limit the concept and scope of the present invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary engineering technicians in the field should fall within the protection scope of the present invention. The technical contents for which protection is sought in the present invention have been fully recorded in the technical requirements.
Claims
1. A method for preparing a lithium ion battery, characterized in that The following steps are involved: (1) preparing a negative electrode sheet for a lithium-ion battery and performing a pre-lithiation treatment on the negative electrode sheet to obtain a pre-lithiation negative electrode sheet; (2) In an inert gas environment, placing the pre-lithiated negative electrode sheet in an electrolyte for reaction, and then washing and drying the pre-lithiated negative electrode sheet to obtain a surface protective layer; (3) The positive electrode active material and the salt solution are fully stirred and mixed, and then filtered, dried and heat-treated in sequence to obtain a modified lithium-ion battery positive electrode sheet; (4) coating the coating slurry on the surface of the microporous membrane material, and then drying and curing the slurry to obtain a lithium-ion battery separator; (5) Assembling the pre-lithiated negative electrode sheet with a surface protective layer, the modified lithium-ion battery positive electrode sheet and the lithium-ion battery separator, and then sequentially performing liquid injection, standing, formation and volume separation treatments to obtain a lithium-ion battery.
2. A method for preparing a lithium ion battery according to claim 1, characterized in that: In the above step (1), the specific process of obtaining the pre-lithiation negative electrode sheet through pre-lithiation treatment is as follows: (1.1) placing the negative electrode sheet of the lithium-ion battery into the first pre-lithiation unit for infiltration treatment; (1.2) placing the negative electrode sheet of the lithium-ion battery after the primary impregnation treatment into the second pre-lithiation unit for secondary impregnation treatment; (1.3) The lithium-ion battery negative electrode sheet after the secondary infiltration treatment is rinsed to obtain a pre-lithiation negative electrode sheet.
3. A method for preparing a lithium ion battery according to claim 2, characterized in that: In the above step (1.1), the temperature environment of the first pre-lithiation unit is 40°C to 85°C, and the negative electrode sheet of the lithium-ion battery is immersed in the first pre-lithiation unit for 20s to 300s.
4. A method for preparing a lithium ion battery according to claim 2, characterized in that: In the above step (1.2), the temperature environment of the second pre-lithiation unit is 20°C to 35°C, and the negative electrode sheet of the lithium-ion battery is immersed in the first pre-lithiation unit for 20s to 360s.
5. A method for preparing a lithium ion battery according to claim 2, characterized in that: In the above step (1.3), dimethyl carbonate solvent is used for elution.
6. A method for preparing a lithium ion battery according to claim 1, characterized in that: In the above step (2), the electrolyte is a mixture of a lithium salt and a solvent, the lithium salt is one or more combinations of lithium hexafluorophosphate, lithium tetrafluoroborate and lithium perchlorate, and the solvent is one or more combinations of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.
7. A method for preparing a lithium ion battery according to claim 1, characterized in that: In the above step (2), the reaction time of the pre-lithiated negative electrode sheet in the electrolyte is 20-60 minutes; the washing times are 3-5 times; the drying temperature is 60°C-70°C, and the drying time is 2-3 hours.
8. A method for preparing a lithium ion battery according to claim 1, characterized in that: In the above step (3), the specific process of obtaining the modified lithium-ion battery positive electrode sheet is as follows: (3.1) The solvent of the salt solution is one or more of methanol and ethanol, and the solute is one or more of lithium, magnesium, aluminum, zinc and chromium, and then the salt solution is prepared, and the concentration of the modified ions in the salt solution is ensured to be 0.1~1.0 mol / L; (3.2) Under continuous stirring, add the salt solution to the positive electrode active material at a rate of 1-10 ml / min, and continue stirring at a stirring rate of 300-1000 r / min for 2-3 hours to obtain the positive electrode material; (3.3) The obtained positive electrode material is first filtered, then dried at a temperature of 50°C to 80°C for 3 to 6 hours, and then heat treated at a temperature of 500°C to 800°C for 3 to 6 hours to obtain a modified lithium-ion battery positive electrode sheet.
9. A method for preparing a lithium ion battery according to claim 8, characterized in that: In the above step (3.2), the positive electrode active material is one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium vanadium phosphate and lithium manganate.
10. A method for preparing a lithium ion battery according to claim 1, characterized in that: In the above step (4), the specific process of obtaining the lithium-ion battery separator is as follows: (4.1) firstly, carbon nanotubes with a diameter of 1 to 250 nm and a length of 0.2 to 50 μm are uniformly dispersed in ethanol to obtain a carbon nanotube dispersion in which the carbon nanotubes account for 1 to 30 wt%; (4.2) then uniformly dispersing aluminum oxide with a particle size of 1 to 500 nm in ethanol to obtain an aluminum oxide dispersion in which the aluminum oxide accounts for 1 to 30 wt %; (4.3) Then, the carbon nanotube dispersion and the aluminum oxide dispersion are fully mixed, and during this process, the mass ratio of the carbon nanotubes to the aluminum oxide is controlled to be 0.5-1, thereby obtaining solution I; (4.4) adding polyvinyl alcohol to solution I, and controlling the amount of polyvinyl alcohol to be 0.1-15 wt % of solution I, thereby obtaining solution II; (4.5) Solution II is then heated to 60°C to 80°C and reacted for 2 to 6 hours to fully crosslink the carbon nanotubes and alumina, and then 0.2 to 1 wt% of sodium dodecyl sulfate is added as an auxiliary agent and stirred for 30 minutes to fully mix the carbon nanotubes and alumina to obtain a coating slurry; (4.6) The obtained coating slurry is coated on the surface of the microporous membrane material, and then dried and cured to obtain a lithium-ion battery separator.